2007
DOI: 10.1677/jme-07-0070
|View full text |Cite
|
Sign up to set email alerts
|

20β-hydroxysteroid dehydrogenase and CYP19A1 are differentially expressed during maturation in Atlantic cod (Gadus morhua)

Abstract: In order to better quantify the molecular mechanisms regulating final oocyte maturation and spawning, complete coding sequences with partially or fully untranslated regions for the steroidogenic enzymes, cytochrome P450 aromatase and 20b-hydroxysteroid dehydrogenase, were cloned from ovaries of Atlantic cod (Gadus morhua). The nucleotide and amino acid sequences showed high homologies with the corresponding sequences of other fish species, and conserved features important for functionality were identified in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…Some studies demonstrated weak 20β-HSD activity of CR/20β-HSD towards 17OHP (7,30), whilst others did not check its activity (28,29,31,32). Moreover, several reports used the gene name 20β-HSD without even using the prefix CR (29)(30)(31). In this study, we do not find support for crediting CR/20β-HSD with MIH production but instead present compelling evidence that 17β-HSD type 12-like is the enzyme responsible for DHP production in masu salmon.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Some studies demonstrated weak 20β-HSD activity of CR/20β-HSD towards 17OHP (7,30), whilst others did not check its activity (28,29,31,32). Moreover, several reports used the gene name 20β-HSD without even using the prefix CR (29)(30)(31). In this study, we do not find support for crediting CR/20β-HSD with MIH production but instead present compelling evidence that 17β-HSD type 12-like is the enzyme responsible for DHP production in masu salmon.…”
Section: Discussioncontrasting
confidence: 81%
“…Since the isolation of a cDNA encoding CR/20β-HSD from pig (4), many studies have targeted CR/20β-HSD orthologs as being responsible for maturation-inducing hormone (MIH) synthesis (7,(28)(29)(30)(31)(32). Some studies demonstrated weak 20β-HSD activity of CR/20β-HSD towards 17OHP (7,30), whilst others did not check its activity (28,29,31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All primer sets were designed to amplify 80-150 bp fragments and verified for target specificity using the NCBI G. morhua nucleotide database. Previously developed assays [49,50] for candidate genes involved in ovarian development were also used, including 20b-hydroxysteroid dehydrogenase (20b-HSD), aromatase (CYP19A1), follicle-stimulating hormone receptor (FSH-R), and luteinizing hormone receptor (LH-R). QPCR primers for cytochrome P450 side chain cleavage enzyme (CYP11A1) were developed from an Atlantic cod cDNA sequence (GenBank Accession # AY706102.1; [23]).…”
Section: Real Time Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…The protocols for quantitative real-time PCR assays for Atlantic cod 20bhsd, cyp19a1a, and for the endogenous control 18s rRNA have been described previously (Mittelholzer et al, 2007). Sequences for all primers and probes are given in Supplement S3.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%